Návrh expanze firmy na zahraniční trh - Dobrovodský, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Diplomová práce se zaměřuje na zhodnocení finanční situace společnosti ESTA, spol. s r. o., která působí na českém trhu v oblasti prodeje přípojkových a distribučních skříní. Cílem práce je navrhnout strategii expanze této společnosti na slovenský trh, a to na základě důkladné analýzy jejího současného stavu. Teoretická část se věnuje metodám finanční analýzy a vybraným nástrojům strategického řízení, jako jsou PESTLE analýza, Porterův model pěti sil, McKinseyho model 7S a SWOT analýza. V praktické části je provedena finanční analýza společnosti a analýza jejího vnějšího i vnitřního prostředí. Tyto analýzy vycházejí z interních účetních výkazů, odborných zdrojů a řízeného rozho-voru s vedením společnosti. Na základě získaných informací je sestavena SWOT analýza. Výsledkem práce je návrh expanze společnosti ESTA, spol. s r. o., na slovenský trh, kte-rý reflektuje aktuální podmínky trhu a přispívá k posílení její strategické pozice na trhu. Návrh zahrnuje marketingovou, finanční a personální strategii i analýzu cílového trhu a potenciálních rizik.

This diploma thesis focuses on evaluating the financial situation of the company ESTA, spol. s r. o., which operates in the Czech market in the field of sales of connection and distribution cabinets. The aim of the thesis is to propose an expansion strategy for the company into the Slovak market, based on a thorough analysis of its current state. The theoretical part is dedicated to financial analysis methods and selected strategic manage-ment tools, such as the PESTLE analysis, Porter’s Five Forces model, McKinsey’s 7S model, and SWOT analysis. The practical part includes a financial analysis of the compa-ny as well as an analysis of its external and internal environment. These analyses are based on internal accounting statements, professional sources, and a structured interview with the company’s management. Based on the collected information, a SWOT analysis is compiled. The outcome of the thesis is a proposal for the expansion of ESTA, spol. s r. o., into the Slovak market, which reflects current market conditions and contrib-utes to strengthening the company’s strategic position. The proposal includes a marketing, financial, and human resources strategy, as well as an analysis of the target market and potential risks.
Proposal for Expansion of the Company to the Foreign Market
Keywords: strategická analýza; finanční analýza; PESTLE analýza; Porterův model pěti sil; McKin-seyho model 7S; SWOT analýza; expanze; zahraniční trh; elektroinstalační materiál; strategic analysis; financial analysis; PESTLE analysis; Porter’s five forces model; McKinsey 7S framework; SWOT analysis; expansion; foreign market; electrical installa-tion material